External coincidence model for hypocotyl thermomorphogenesis. (3rd April 2018) - Park, Young-Joon; Park, Chung-Mo
ABSTRACT: High but nonstressful temperatures profoundly affect plant growth and developmental processes, termed thermomorphogenesis. Thermo-induced hypocotyl elongation is a typical thermomorphogenic trait, which contributes to cooling plant organs. It is known that external light signals and the circadian clock coordinate rhythmic hypocotyl growth. However, it was unclear how light, temperature, and circadian rhythms are harmonized during hypocotyl thermomorphogenesis. We have recently demonstrated that the E3 ubiquitin ligase CONSTITUTIVE PHOTOMORPHOGENIC 1 (COP1) is activated at warm temperatures. It is notable that warm temperatures induce the nuclear import of COP1, facilitating degradation of ELONGATED HYPOCOTYL 5 (HY5) and this biochemical event is uncoupled from light conditions. Furthermore, the thermo-induced HY5 protein turnover occurs independent of circadian rhythms, indicating that the COP1-HY5 module conveys warm temperature information. Meanwhile, the clock components, including CIRCADIAN CLOCK ASSOCIATED 1 (CCA1), convey timing information for the rhythmic thermomorphogenic growth. These molecular mechanisms enable a coincidence between warm temperature signaling and circadian rhythms, which explains the distinct rhythms of hypocotyl growth at warm temperatures.